1993
DOI: 10.1016/s0022-5347(17)36021-4
|View full text |Cite
|
Sign up to set email alerts
|

Mature Testicular Teratoma with Vena Caval Invasion Presenting as Pulmonary Embolism

Abstract: We report a case of mature testicular teratoma with invasion and thrombosis of the inferior vena cava that presented as recurrent pulmonary embolism. Treatment included radical orchiectomy, chemotherapeutic cytoreduction and, finally, resection of a massive retroperitoneal tumor with en bloc resection of the inferior vena cava using cardiopulmonary bypass and deep hypothermic circulatory arrest. Management is discussed and the literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…As Kwok et al [5] reported, our patient showed a marked discor dance between the severity of the pulmonary embolism and the absence of evidence of metastatic spread. Moreover, in addition to having the spermatic cord, tunica albuginea and epididymis all free of tumor, the patient ultimately responded well to chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…As Kwok et al [5] reported, our patient showed a marked discor dance between the severity of the pulmonary embolism and the absence of evidence of metastatic spread. Moreover, in addition to having the spermatic cord, tunica albuginea and epididymis all free of tumor, the patient ultimately responded well to chemotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…Neoplastic pulmonary embolism has rarely been re ported, and most cases were from autopsy studies [1,4]. To our knowledge, only 4 cases have been clinically recognized and in only 1 case was pulmonary embolism the initial symptom [3,[5][6][7], We report here the exceptional case of a nonseminomatous germ cell tumor presenting as a dramatic neoplastic pulmonary embolism treated by surgical thrombectomy, with excellent outcome.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Renal cell carcinoma is the most common cause, 1 but germ cell tumor, retroperitoneal leiomyosarcoma, adrenal cortical carcinoma, renal angiomyolipoma, and hepatic hemangioma have been reported as other causes. [2][3][4][5][6][7] In this case, a germ cell tumor was associated with IVC thrombosis. Germ cell tumor is the most frequent malignancy in men aged 18-35 years.…”
Section: Discussionmentioning
confidence: 99%
“…4 -11 Because of the rapid shrinkage of large tumor masses that can occur during chemotherapy, there is the possibility of significant morbidity and mortality from pulmonary embolism in patients with IVCO. 4,5,18 We have described 31 cases of IVCO secondary to metastatic GCT. Approximately 33% of patients with IVCO secondary to metastatic GCT had thromboembolic complications, with 1 case of fatal pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%